Pengaruh Elemen Paduan dan Senyawa terhadap Karakteristik Paduan Magnesium dan Aplikasinya - Kajian - Adi Ganda Putra; Azwar Manaf; Djoko HP (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2021)
Alloys based on Magnesium the lightest structural metal and Mg have great application potential in the automotive and aerospace industries. However, Magnesium in its application is limited by its low strength and ductility. The most effective way to increase strength and ductility is by adding alloying elements, grain refinement, and dispersion strengthening. However, universal strengthening techniques for magnesium alloys are still being researched, and some are still being debated. This paper presents a brief overview of the development of methods of adding alloying elements to magnesium alloys, contributing to a better understanding of the factors controlling mechanical properties and providing an outlook for future research in this area.